FOSTERING CREATIVE THINKING AND INNOVATION IN CLUB ACTIVITIES: METHODS AND TECHNOLOGIES - Boymatov Baxrom Eshmamatovich (Bright Mind Publishing, 2026)
This article examines methods and technologies for developing creative thinking in extracurricular club activities. It focuses on creative pedagogy and interactive, student-centered approaches that promote independent thinking and innovative problem-solving. Methods such as debates, brainstorming, mind mapping, and project-based learning are presented as effective tools for fostering creativity. The study emphasizes that well-structured and technology-supported club activities create favorable conditions for developing creative and socially active learners.
Keywords: Creative thinking, club activities, creative pedagogy, interactive learning, debate, brainstorming, mind mapping, project-based learning.